MENINGKATKAN HASIL BELAJAR ENTRY JURNAL MELALUI MODEL PROJECT BASED LEARNING DI SMP - Uni, Yulia (Universitas Tanjungpura, 2021)
The purpose of this study was to determine the improvement in accounting learning achievement for class X accounting students at SMKN 1 Sanggau Ledo through project-based learning model. This research is classroom action research (CAR) to overcome the problems existing in the classroom.The research subjects used were students of class X Accounting at SMKN 1 Sanggau Ledo in the odd semester of the 2018/2019 academic year, 18 students. The research was conducted in two cycles and each cycle reflected on the given action. Data collection techniques used observation sheets,learning achievement tests, project assignments and documentation. The method for data analysis is descriptive quantitative analysis. The results of the study indicated that the implementation of learning through project based learning model in accounting subjects for journal entry materialscan improve learning activities and students’ learning achievement. This can be seen from the students’ learning achievement in the first cycle of 55.56% and increased in the second cycle to 83.33%. students’ learning achievement in cycle 1 with the average class was 63.56 where 10 students completed, out from from 18 students. While in cycle 2 the average class of students’learning achievement was 80.89 with 15 students whose grades that were declared to have been completed. The conclusion that can be drawn is that the application of the project based learning model has succeeded in increasing the learning achievement of accounting for journal entry materials so that it is feasible to be applied at SMKN 1 Sanggau Ledo.